Harper's illustrated biochemistry - Murray, Robert K.; Bender, David A.;Botham, Kathleen M.;Kennelly, Peter J.;Rodwell, Victor W.;Weil, P. Anthony (New York : McGraw Hill Education, 2009)
With a combination of case studies, discussions of biochemical diseases, updated clinical information, and frequent revision, this is an indispensable book for students of biochemistry. The Twenty-Eighth Edition has undergone sweeping changes -- including a conversion to full-color artwork and the substantial revision and updating of every chapter -- all to reflect the latest advances in knowledge and technology and to make the text as up-to-date and clinically relevant as possible. Combining outstanding full-color illustrations with integrated coverage of biochemical diseases and clinical information, Harper's Illustrated Biochemistry offers an organization and clarity not found in any other text on the subject. Striking just the right balance between detail and brevity, Harpers Illustrated Biochemistry is essential for USMLE review and is the single best reference for learning the clinical relevance of a biochemistry topic.
Biochemistry & medicine -- Water & pH -- Amino acids & peptides -- Proteins: determination of primary structure -- Proteins: higher orders of structure -- Proteins: myoglobin & hemoglobin -- Enzymes: mechanism of action -- Enzymes: kinetics -- Enzymes: regulation of activities -- Bioinformatics & computational biology -- Bioenergetics: the role of ATP -- Biologic oxidation -- The respiratory chain & oxidative phosphorylation -- Carbohydrates of physiologic significance -- Lipids of physiologic significance -- Overview of metabolisms & the provision of metabolic fuels -- The citric acid cycle: the catabolism of acetyl-CoA -- Glycolysis & the oxidation of pyruvate -- Metabolism of glycogen -- Gluconeogenesis & the control of blood glucose -- The pentose phosphate pathway & other pathways of hexose metabolism -- Oxidation of fatty acids: ketogenesis -- Biosynthesis of fatty acids & eicosanoids -- Metabolism of acylglycerols & sphingolipids -- Lipid transport & storage -- Cholesterol synthesis, transport, & excretion -- Biosynthesis of the nutritionally nonessential amino acids -- Catabolism of proteins & of amino acid nitrogen -- Catabolism of the carbon skeletons of amino acids -- Conversation of amino acids to specialized products -- Porphyrins & bile pigments -- Nucleotides -- Metabolism of purine & pyrimidine nucleotides -- Nucleic acid structure & function -- DNA organization, replication, & repair -- RNA synthesis, processing, & modification -- Protein synthesis & the genetic code -- Regulation of gene expression -- Molecular genetics, recombinant DNA, & genomic technology -- Membranes: structure & function -- The diversity of the endocrine system -- Hormone action & signal transduction -- Nutrition, digestion, & absorption -- Micronutrients: vitamins & minerals -- Free radicals and antioxidant nutrients -- Intracellular traffic & sorting of proteins -- Glycoproteins -- The extracellular matrix -- Muscle & the cytoskeleton -- Plasma proteins & immunoglobulins -- Hemostasis & thrombosis -- Red & white blood cells -- Metabolism of xenobiotics -- Biochemical case histories.
Includes bibliographical references and index.
Keywords: BIOCHEMISTRY